The effects of the socioeconomic status of Serbian families with coeliac children on gluten-free diet - stojanović, biljana n; stojanović, biljana n (Medicinski časopis, 2018)
Objective: To determine the effects of the socioeconomic characteristics of Serbian families with coeliac children (education level, employment, number of family members, monthly family income) on a gluten-free diet outcomes, as measured by serologic tests (tTG). Methods: The sample included 116 parents and the same number of children and adolescents (N = 116) diagnosed with the coeliac disease who had followed a gluten-free diet for at least a year. Children were aged 5-18 years. The research was carried out at the University Children's Hospital in Belgrade and the Institute of Mother and Child Health "Dr Vukan Čupić" in Belgrade. The research was conducted during the period April-December 2016. The instruments used in the research were the Socioeconomic Survey Questionnaire and the Documentation Sheet, both specially designed for the purpose of this study. Results: The results of our study have shown that the mean age of mothers was 39.6 years and fathers 43.4 years. Parent respondents reported completed secondary education in 58% (116) of all cases. 46.55% of mothers and 35.34% fathers of the examined children with coeliac disease were not permanently employed. 82.76% of parents were married. Four-member families were most common. Considering the specific needs, 51% of the parents perceived their income level as very low and low. Serologic tests confirmed the efficacy of the therapy in 25.86% (30/116) of the children. Conclusion: The poor success of a gluten-free diet in the coeliac children and adolescents pointed out to the major impact of a lower socioeconomic status of their families. Taking into account all the difficulties in the implementation of a gluten-free dietary restrictions for children in Serbia, it becomes clear that the engagement of the whole society, and not just the members of their families, is necessary. Key words: Coeliac disease, children, gluten-free diet, quality of life